Analysis of local chronic inflammatory cell infiltrate combined with systemic inflammation improves prognostication in stage II colon cancer independent of standard clinicopathologic criteria. Issue 3 (2nd September 2015) - Turner, Natalie; Wong, Hui‐Li; Templeton, Arnoud; Tripathy, Sagarika; Whiti Rogers, Te; Croxford, Matthew; Jones, Ian; Sinnathamby, Mathuranthakan; Desai, Jayesh; Tie, Jeanne; Bae, Susie; Christie, Michael; et al.
Abstract : In Stage II colon cancer, multiple independent studies have shown that a dense intratumoural immune infiltrate (local inflammation) is associated with improved outcomes, while systemic inflammation, measured by various markers, has been associated with poorer outcomes. However, previous studies have not considered the interaction between local and systemic inflammation, nor have they assessed the type of inflammatory response compared with standard clinicopathologic criteria. In order to evaluate the potential clinical utility of inflammatory markers in Stage II colon cancer, we examined local and systemic inflammation in a consecutive series of patients with resected Stage II colon cancer between 2000 and 2010 who were identified from a prospective clinical database. Increased intratumoural chronic inflammatory cell (CIC) density, as assessed by pathologist review of hematoxylin and eosin stained slides, was used to represent local inflammation. Neutrophil‐to‐lymphocyte ratio (NLR) >5, as calculated from pre‐operative full blood counts, was used to represent systemic inflammation. In 396 eligible patients identified, there was a non‐significant inverse relationship between local and systemic inflammation. Increased CIC density was significantly associated with improved overall (HR 0.45, p = 0.001) and recurrence‐free survival (HR 0.37, p = 0.003). High NLR was significantly associated with poorer overall survival (HR 2.56, p < 0.001). The combination of these markers further stratified prognosis independent of standard high‐risk criteria, with a dominant systemic inflammatory response (low CIC/high NLR) associated with the worst outcome (5‐year overall survival 55.8%). With further validation this simple, inexpensive combined inflammatory biomarker might assist in patient selection for adjuvant chemotherapy in Stage II colon cancer. Abstract : What's new? Routine use of adjuvant chemotherapy is not recommended for Stage II colorectal cancer (CRC). However, there appears to be a subgroup of patients with a higher than usual risk of recurrence. In this study, the authors found that markers of inflammation, including neutrophil‐to‐lymphocyte ratio (NLR) and density of chronic inflammatory cell infiltrate (CIC) have prognostic value in Stage II CRC. These results suggest that a simple, inexpensive assay for this combination of inflammatory biomarkers might aid in selecting those patients that would benefit from adjuvant chemotherapy.